HUBUNGAN CARE FAMILY PADA HOMECARE DENGAN KEPATUHAN DIET RENDAH GLUKOSA PADA PASIEN DIABETES MELLITUS TIPE II DI WILAYAH KERJA PUSKESMAS MOCONGLOE - Zaenal; Baso Witman Adiaksa (Stikes Graha Edukasi Makassar, 2022)
The purpose of this study was to determine the relationship between Care family in Homecare and adherence to a low glucose diet at the Moncongloe Health Center. Methods: This research is a quantitative research. The design of this study used a non-experimental research method which is a type of analytic research with a cross sectional approach. The sampling technique used consecutive sampling technique, namely the sample size in this study was 32 respondents who matched the inclusion criteria. Data collection was carried out by distributing questionnaires, where to see the relationship between family support and adherence to a low-glucose diet in patients with type I diabetes mellitus. Results: This study uses Chi-square test with fisher's exact test correction, at the significance level = 0.05. Based on the results of the study, it was found that there was a relationship between Care family in Homecare and adherence to a low glucose diet in the working area of ??the Moncongloe Health Center (p = 0.03). Discussion: In creating compliance there needs to be collaboration between health workers and the environment with DM patients so that they can create motivation and support from outside. Conclusion: The conclusion in this study is that there is a relationship between family support and adherence to a low-glucose diet. Suggestion: To health workers, especially nurses in order to improve patient compliance in treatment and diet should always provide health education about the concept and management of type II diabetes mellitus